PENGARUH ARUS KAS AKTIVITAS OPERASI, LABA BERSIH DAN TINGKAT LIKUIDITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI – KOSMETIK DAN RUMAH TANGGA, PERALATAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2022 - Rahayu, Sri; Nur Aini Winda, Lestari (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
This research aims to determine the effect of the Operating Activity Cash Flow variable, the Net Profit variable, and the Liquidity Level variable using the Current Ratio (CR) on Stock Prices. The data source used in this research is secondary data obtained from the Annual Financial Reports of Companies in the Consumer Goods Industry Sector - Cosmetics and Households, Household Appliances Listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period from the official websites of the relevant companies. The sampling method uses the Purposive Sampling method. The hypothesis testing method for this research uses Multiple Linear Regression Analysis, Classical Assumption Test, t Test, F Test, and Coefficient of Determination Test (R2).The results of the t test research (partial) show that (1) Cash Flow from Operating Activities has a significant effect on Stock Prices with a significance value of 0.008 < 0.05 and tcount 2.850 > ttable 2.05553. (2) Net Profit has a significant effect on Stock Prices with a significance value of 0.035 < 0.05 and tcount 2.223 > ttable 2.05553. (3) Current Ratio (CR) has a significant effect on Stock Prices with a significance value of 0.002 < 0.05 and tcount 3.456 > ttable 2.05553. Meanwhile, the results of the F test (simultaneous) of cash flow from operating activities, net profit and current ratio (CR) have a significant effect on Stock Prices with a significant level of 0.000 < 0.05 and Fcount = 22.517 > Ftable where the value. The Ftable obtained from n = 30 and K = 3 is 2.96.